Axial compression damage constitutive model and damage characteristics of fly ash/silica fume modified magnesium phosphate cement after being treated at different temperatures - Guo Boyu; Zhu Jincai; Meng Xiaokai; Cao Qi (Reviews on Advanced Materials Science)
The relationship between fly ash (FA) and silica fume (SF)-modified magnesium phosphate cement (MPC) at varying temperatures remains unclear. In this study, the mechanical properties and damage characteristics of FA- and SF-modified MPC at 20–1,000°C were analysed through uniaxial compression tests. The results indicate that the compressive strength of MPC diminishes at varying temperatures, while FA and SF can enhance the compressive strength of MPC following exposure to high temperatures. In addition, with an increase in the temperature, the peak strain of MPC increased, and the deformation modulus first decreased and then increased. At 1,000°C, the deformation modulus of MPC was 5.09–10.92 GPa. The proposed damage constitutive model can predict the mechanical parameters of FA- and SF-modified MPC at different temperatures. The total damage variable reflects an “S-shaped” change trend under the action of axial compression loads. MPC exhibited irreversible initial temperature damage after being treated at different temperatures. More specifically, the temperature damage variable first increased and then decreased by increasing the temperature. At 600°C, the temperature damage variable exceeds 30% of the total damage variable associated with the peak strain, and at 1,000°C, it surpasses 10%.